Prevalence of Hypertension among the Patients Who Attend Medicine Outdoor of Dhaka Medical College Hospital - Kabir, Ahmedul; Barman, Tushar Kanti; Yousuf, Nusrat Ara; Fatima, Nusrat; Banik, Jayanta (Journal of Medicine, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Introduction: Worldwide, Hypertension is the established risk factor for many premature cardiovascular morbidity and mortality. Prevalence of hypertension depends on both the racial composition of the population and the criteria used to define the condition and on how extensively the evaluation I done. Objective: To find out the Prevalence of hypertension and also the variation of Prevalence of hypertension, at different age group, rural to urban population, association with other medical conditions and family history of hypertension among the patients who come to seek treatment in Medicine OPD, Dhaka Medical College Hospital. Materials and Methods: This prospective study was carried out in the medicine outdoor of Dhaka Medical College Hospital during the whole month of July'2007. The patients who attend medicine OPD, DMCH during the month of July'2007 to seek medical treatment were included in the study. Exclusion criteria was who denied to measure Blood pressure or non cooperation of the patient. The diagnosis and classification of hypertension was done according to the JNC-7 report. A subject was considered hypertensive if one has an average SBP >140 mm of Hg of DBP>90 mm of Hg or if he/ she was already diagnosed as a hypertensive with or without anti-hypertensive medication. Blood pressure (BP) was measured twice in two arms by using sphygmomanometer. Among the newly detected hypertensive patients, blood pressure was again measured after 15 minutes of rest in handled chair, in calm environment. After second measurement if BP is still more than or equal to 140/90 mmHg, they were detected as hypertensive. After detecting hypertensive patient, their all data are recorded in a structured questionnaire. Results: After proper measurement of BP of 17,792 patients, hypertension was found in 554 patient (3.11%) of them 181 were male (32.67%) and 373 were female (67.33%). So, Prevalence of hypertension among the patient who attend medicine outdoor of DMCH is about 3.11% and slight this female predominance. Conclusion: This data may not exactly reflect the actual Prevalence of hypertension as it is outdoor hospital based but give an idea about the Prevalence of hypertension among the patient who attend for treatment in a tertiary based hospital. Â Â  DOI = 10.3329/jom.v8i2.1406 J MEDICINE 2007; 8 : 49-52